2001
DOI: 10.1128/jb.183.16.4839-4847.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Antigenic, and Functional Analyses of Omp2b Porin Size Variants of Brucella spp

Abstract: Omp2a and Omp2b are highly homologous porins present in the outer membrane of the bacteria from the genus Brucella, a facultative intracellular pathogen. The genes coding for these proteins are closely linked in the Brucella genome and oriented in opposite directions. In this work, we present the cloning, purification, and characterization of four Omp2b size variants found in various Brucella species, and we compare their antigenic and functional properties to the Omp2a and Omp2b porins of Brucella melitensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
1
39
0
5
Order By: Relevance
“…However, in a planar lipid bilayer study, Omp2a behaved in a rather anomalous manner, in contrast to Omp2b, which produced conductance steps expected for stable, trimeric porins (424). In any case, the juxtaposition of two very homologous genes apparently produces constant variation in gene sequences via gene conversion mechanism (482), and the effect of this variation on the physiology and evolution of Brucella species remains an interesting topic. OM protein IIIa of Rhizobium leguminosarum is homologous to Brucella porins (128), but no further study of the Rhizobium porin seems to exist.…”
Section: Other Porinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a planar lipid bilayer study, Omp2a behaved in a rather anomalous manner, in contrast to Omp2b, which produced conductance steps expected for stable, trimeric porins (424). In any case, the juxtaposition of two very homologous genes apparently produces constant variation in gene sequences via gene conversion mechanism (482), and the effect of this variation on the physiology and evolution of Brucella species remains an interesting topic. OM protein IIIa of Rhizobium leguminosarum is homologous to Brucella porins (128), but no further study of the Rhizobium porin seems to exist.…”
Section: Other Porinsmentioning
confidence: 99%
“…The proposal made by Ferenci was to look at the alignment of related porin sequences and assume that the less variant regions correspond to transmembrane strands. This works very nicely when many sequences from isolates of the same species, for example, exist (362,482). However, in other cases one has to start from an alignment of sequences of distantly related porins, and this requires the prior identification of transmembrane strands.…”
Section: Classical Porinsmentioning
confidence: 99%
“…Indeed, pores are larger in Omp2a than in its homologue Omp2b (85% sequence identity and both encoded in the same genetic locus). 27 Although the function of Omp2a is still poorly understood at the structural level, as the 3D structure of Brucella β-barrel MPs is not known yet, very recent refolding studies suggested that Omp2a first refolds under a monomeric form and then self-associates into a trimeric state. 28,29 On the other hand, poly(N-methylpyrrole) (PNMPy) is the CP chosen to act as the supporting matrix for Omp2a.…”
Section: Introductionmentioning
confidence: 99%
“…T demonstrated close clustering to an atypical B. suis strain (strain 83-210) isolated from a rodent in Australia (30,44). Further genetic analysis of the 16S rRNA genes from strains BO1…”
mentioning
confidence: 99%